CREDIT RISKS AND MANAGEMENT STRATEGIES OF COMMERCIAL BANKS IN UZBEKISTAN - Kholdorov , Sardor (Insurance market of Uzbekistan, 2024)
This study looks at the credit risks and risk management techniques used by Uzbek commercial banks. The study investigates a number of management techniques to reduce these risks, including strengthening loan monitoring systems, refining credit risk assessment frameworks, and moving state-owned banks toward more commercially oriented business models. This thorough study offers insightful information about the difficulties and approaches associated with credit risk management in the developing financial environment of Uzbekistan.